The Horn of Africa since the 1960s: Local and International Politics Intertwined - Ylönen, A.; Záho?ík, J. (2017)
The Horn of Africa has long been one of the most dynamic and politically turbulent sub-regions on the African continent. Host to great ancient civilizations, diverse peoples, and expansive states, it has experienced massive social, economic, and political transformation over time. Political dynamics in this region have generated military coups, revolutions and intractable ethnic, socio-economic, and religious conflicts. This comprehensive volume consists of a collection of chapters by expert African and international scholars who analyze international, regional, national, and local affairs in the sub-region, which demonstrate the intertwined nature of the actors and forces shaping political realities. The contributions include carefully selected case studies of Ethiopia, Eritrea, Somalia, Somaliland, Sudan, and South Sudan that eloquently illustrate the complex dynamics connecting a spectrum of political issues. The Horn of Africa since the 1960s will be of interest to students and scholars of African studies in general, diaspora studies, sociology and comparative politics.